Resection of biliary convergence cancer superior (Klatskin tumors).: About a new series - Praderi, Raúl C; Parodi, Hernán; del Campo, Francisco; Navarrete, Héctor; Tiscornia, Eduardo; Praderi, José A; Fernández, Gonzalo; Farcic, Antonio (Cirugía del Uruguay, 1998)
The authors present a series of nine patients with cancer of the upper biliar 'convergen ce (Klatskin tumors). They underwent surgery between 1984 and 1997. Tumors were total/y resected including two, three or tour biliar conducts. In three cases right hepatectomy was a/so performed. In al! cases two or three biliojejunal anastomosis over diverticular ansa with our modification of the Hivet-Warren anastomosis were performed.